Analyzing Generation Z Turnover Intention: The Effect of Learning Agility and Psychological Capital - Esterina, Meriam; Hidayati, Wahyu Risma Nur; Wicaksono, Bagus Satrio (PT FORMOSA CENDEKIA GLOBAL, 2025)
Generation Z with its unique characteristics has attracted much attention due to its suboptimal performance resilience. The rise in turnover intention among generation Z needs to be a concern. This study aims to determine the influence of learning agility and psychological capital factors on turnover intention among generation Z. The research employs a quantitative approach with correlational design, utilizing convenience sampling technique to collect data from 454 generation Z employees (70% female, 30% male) across various industrial sectors in Indonesia. Data collection was conducted through online surveys using three validated instruments: PCQ-24 to measure Psychology Capital, De Meuse's Learning Agility scale, and Mobley's Turnover Intention scale. Data analysis using JASP 0.19.0.0 software revealed that Psychology Capital and Learning Agility collectively explain 63.5% of variance in Turnover Intention (R² = 0.635, p < 0.001). Learning Agility emerged as the dominant predictor, contributing 61.3% to Turnover Intention variance, while Psychology Capital showed minimal contribution of 0.5%. These findings indicate that adaptability and learning capabilities significantly influence generation Z employees' intention to leave their jobs.